2019
DOI: 10.34050/els-jish.v2i3.7955
|View full text |Cite
|
Sign up to set email alerts
|

Function of Code Switching Performed by the EFL Teachers in Classroom Interaction

Abstract: The objective of this research is to determine the functions of code switching performed by the EFL teachers in classroom interaction. This research used qualitative research design which was conducted in SMAN 1 Soppeng. The participants of this research were two English teachers of SMAN 1 Soppeng who were chosen by using purposive sampling technique. To collect the data, the researcher used two kinds of research instrument namely classroom observation and interview. The data obtained were analyzed through Mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…This issue is considered by other researchers as well. In their work titled "An Investigation of the Use of CS in EFL Classroom: Attitudes and Perceptions," Patmasari et al, (2022) considered this issue alongside teachers' perceptions on CS. The chosen participants who were interviewed revealed that they had favorable views and opinions about CS in EFL classrooms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This issue is considered by other researchers as well. In their work titled "An Investigation of the Use of CS in EFL Classroom: Attitudes and Perceptions," Patmasari et al, (2022) considered this issue alongside teachers' perceptions on CS. The chosen participants who were interviewed revealed that they had favorable views and opinions about CS in EFL classrooms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The use of English in foreign language countries, especially in Indonesia has become an important issue for both the lecturers and learners. In Indonesia, English is frequently taught as a foreign language, and it typically holds official status inside the country [1].Students are required to acquire the language because it comprises one of the required courses at their school. In English as Foreign Language (EFL) Classroom, lecturers teach and students learn English whereas there is limited use of English in their daily social interaction.…”
Section: Introductionmentioning
confidence: 99%
“…The practice of shifting from one language to another could not be avoided by both the lecturers and students in the EFL classroom. The process of shifting language requires the teachers and students to be bilingual and maintain two languages with the intention of better comprehension [1], [4]. The teaching of languages should encourage bilingual or multilingual people to use every aspect of their linguistic resources to learn another language, a process known as translanguaging.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation on CS in the EFL classroom practices continue up to present era. The more recently study were conducted by Huda, Hakim, & Mizam (2020), Tyas (2020), Patmasari & Agussatriana (2019), Narasuman, Wali, & Sadry (2019). It bears out that research on SC is still relevant and interesting to be carried out in that each of the study has its own uniqueness.…”
Section: Introductionmentioning
confidence: 99%